TOURISM DISCOURSE LANGUAGE AND GLOBAL MOBILITY: AN ANALYSIS OF ASSOCIATED IMPACTS - Khakimova , Zukhra Bakhodirovna (Innovative Development in Educational Activities, 2024)
Tourism discourse language plays a pivotal role in shaping the global mobility landscape, influencing individuals’ perceptions, attitudes, and behaviors towards travel and cultural exploration. This scientific article provides a comprehensive analysis of the intricate relationship between tourism discourse language and global mobility. It delves into the linguistic constructs, cultural implications, and socio-economic impacts associated with the use of language in tourism discourse. By examining various linguistic strategies, cultural nuances, and societal dynamics, this article aims to elucidate the profound interplay between language and global mobility in the context of tourism.